Pengaruh Merger dan Akuisisi terhadap Acquirer Firm’s Financial Performance - Yosephine Kurnia Anggita; Juniarti Juniarti; Angeline Angeline (Business Accounting Review, 2021)
The increase of merger and acquisition activities are enhancing the development of technology sectors significantly. Previous literature regarding the impacts of mergers and acquisitions on firm's financial performance has contradictory results between the positive and negative impacts. Therefore, this study aims to search the impact of mergers and acquisitions on acquirer firm's financial performance. The technology sector is chosen in this study as studies regarding financial performance in this sector are few. In this study, the acquirer firm's financial performance is measured using Return on Asset (ROA). The data used in this study is companies' data from the technology sector that have merger and acquisition transactions from 2014 through 2018. To be included as a sample, the company must be registered as a public company and have a headquarter in Asia. Ordinary Least Square (OLS) is used as the data analyzing method used in this study. The findings suggest that mergers and acquisitions have a positive and statistically significant impact on acquirer firm’s financial performance. The control variables in this study, which are firm age and leverage, are shown to have a negative and significant effect on acquirer firm’s financial performance. Whilst firm size is shown to have a positive effect but the effect is not statistically significant. Due to restrictions in accessing internal company's data, this study could only be conducted on public companies. This study contributes to previous literature by adding new empirical evidence regarding the impact of merger and acquisition on firm’s financial performance in the technology sector.